Utilization Of Kuku Pancar (Lawsonia Inermis Lin) Leaves as a Substitute For Eosin Dye in The Examination of Soil Transmitted Helminth (STH) Eggs - Yusari, Lala Deswinta; Srigede, Lalu; Manu, Thomas Tandi; Khusuma, Ari (Poltekkes Kemenkes Mataram, 2024)
Nail surfacing leaves (Lawsonia inermis lin) are natural materials commonly used as dyes, because of the content of chemical compounds in them such as lawsone, flavonoids, tannins and anthocyanins, therefore nail surfacing leaves can be used as an alternative dye to replace 2% Eosin in STH worm egg examination, because it has the same properties as 2% Eosin and can produce an orange yellow color after the extraction process. The research objective is to determine the results of nail surfacing leaves (Lawsonia inermis lin) can be used as an alternative substance to replace Eosin in the examination of STH (soil transmitted helminth) worm eggs. The methods of this research is using is experimental, where this study looks at the clarity of soil transmitted helminth (STH) worm eggs on preparations, using coloring from the results of soaking the leaves of the nail surf as a substitute for Eosin. The results of the research is that the coloring results obtained in each variation of immersion time are good. The conclusion of this research is that the staining of worm eggs using the results of immersion of nail surfacing leaves for 12 hours, 24 hours, 36 hours, and 48 hours can be used as an alternative dye in the examination of STH worm eggs.